2019
DOI: 10.5114/wiitm.2019.89653
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ultrasound guided ganglion stellate blockade on intraoperative and postoperative hemodynamic responses in laparoscopic gynecologic surgery.

Abstract: Introduction: Laparoscopic gynecologic surgery is one of the most well-known procedures. Pneumoperitoneum with carbon dioxide insufflation can cause unfavorable hemodynamic effects due to catecholamine and vasopressin release. Aim: To examine the effects of stellate ganglion block on hemodynamic response and postoperative pain. Material and methods: In a prospective double blinded randomized parallel study we included 40 patients with ASA physical status I and II, aged between 18 and 50 years with a gynecologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 20 publications
0
19
0
Order By: Relevance
“…It seems most successful in the early stages, as we could show ( Schaible and Straub, 2014 ; Strong et al, 2018 ). Other studies have also shown a time-dependent effect of SGB ( Rahimzadeh et al, 2020 ).…”
Section: Why a Stellate Ganglion Block (Sgb)?mentioning
confidence: 82%
See 1 more Smart Citation
“…It seems most successful in the early stages, as we could show ( Schaible and Straub, 2014 ; Strong et al, 2018 ). Other studies have also shown a time-dependent effect of SGB ( Rahimzadeh et al, 2020 ).…”
Section: Why a Stellate Ganglion Block (Sgb)?mentioning
confidence: 82%
“…There are further examples: In a prospective, double blinded randomized parallel study SGB applied before laparoscopic gynecologic surgery decreased pain significantly immediately after surgery ( Rahimzadeh et al, 2020 ). Postoperative pain always has an inflammatory component.…”
Section: Why a Stellate Ganglion Block (Sgb)?mentioning
confidence: 99%
“…The trials included in the present study were published between the years 2004 and 2022, and their sample sizes ranged from 30 to 90. The trials investigated the effects of SGB in patients who underwent various kinds of surgeries: breast surgeries in three studies, 15 17 abdominal surgeries in two studies, 13 , 14 and upper limb and thoracoscopic surgeries in the remaining studies. 11 , 12 Five studies compared SGB with placebo, 11 , 13 , 14 , 17 , 18 and two studies compared SGB with multimodal systemic analgesia or PCA.…”
Section: Resultsmentioning
confidence: 99%
“…SGBs may be more effective if administered as soon as possible after the onset of symptoms, as suggested by several studies for anosmia and dysgeusia not related to COVID-19. 14,[32][33][34] Although the research cited and reported in this review indicated successful SGB treatment as far as 6 months after symptom onset, further research is needed to identify whether or not such a temporal limitation exists.…”
Section: Limitations and Potential Complicationsmentioning
confidence: 90%